DARI PITHECANTHROPUS KE HOMO ERECTUS: SITUS, STRATIGRAFI, DAN PERTANGGALAN TEMUAN FOSIL MANUSIA DI INDONESIA - Widianto, Harry (BRIN, 2006)
More than 100 ancient human individuals were shown from various ancient deposits on the island of Java, whose sites are located in various physiographic landscapes, namely: the Solo basin (Sangiran and Miri), the volcanic deposits of the Kendeng Mountains (Trinil, Kedungbrubus, and Perning in Mojokerto), the Bengawan Solo alluvial deposits (Ngandong, Sambungmacan, and Ngawi), and the volcanic deposits of Mount Muria (Patiayam). Human migration on the island of Java is thought to have only taken place in the Lower Plestocene from mainland Asia, which probably originated in Africa.